Isolation and identification of Steroids from Different Parts of Prosopis Cineraria - Preeti Khandelwal (Journal of Global Pharma Technology, 2017)
Prosopis cineraria are a tree of remarkable importance and a rich   source of secondary metabolites. The present study was carried out to investigate   the steroid content   present in the leaves, stem and pods of Prosopis cineraria. The   method of Tomita et al., was used   for isolation of steroids.  The  structure  of  the  isolated  compound  was  established  on  the  basis  of  physical  and  chemical  test   and  spectroscopic  evidences (TLC, IR and  GC- MS). The study concluded   that a single type of steroid Diosgenin was found in all the parts of the selected plant species.Keywords: Prosopis cineraria; Steroids; Diosgenin; Thin Layer Chromatography.